The Effect of Skill Exercises on Some Bio-kinetic Abilities and Developing the Basic Skills of Emerging Football Players - Mohammed Ashour Abbas (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The purpose of this paper is to be preparing skill exercises to train some basic skills for emerging football players and identify the effect of skill exercises on bio-kinetic abilities and develop some basic skills for emerging football players. The researcher used the method the experimental method was conducted in two equal groups with pre- and post-tests to suit the research problem. The researcher selected a population of (40) players emerging from the Specialized Center for Nurturing Sports Talent in Football. The sample was divided into two experimental and control groups, as the number of students in the experimental group reached (15) players, while the group the number of players has reached (15) . One of the most important results reached by the researcher is that: The training program prepared by the researcher suits the skill exercises for the research sample, who are emerging football players, and there is a noticeable development in the level of bio-kinetic abilities and basic football skills among the research sample and for the experimental and control groups. According to these conclusions. One of the most important recommendations recommended by the researchers is that: Using the program and skill exercises used in the current research to conduct other studies and experiments on other age groups and introducing trainers into development courses that consider the use of modern and advanced methods in training, especially training age groups.